2022
DOI: 10.2196/38133
|View full text |Cite
|
Sign up to set email alerts
|

Applying Gamification Principles and Therapeutic Movement Sequences to Design an Interactive Physical Activity Game: Development Study

Abstract: Background Depression is a severe illness that has accelerated with the spread of COVID-19 and associated lockdowns. As a result, reported physical activity has substantially decreased, further increasing depressive symptoms. Objective This study aims to explain the use of gamification principles to develop content for an interactive physical activity game for depression based on clinically proven depression diagnostic criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Recruitment and compliance [ 28 ], accessibility to technology and digital literacy [ 30 ], user responsiveness in particular contexts [ 22 ], ethical concerns [ 17 ], and the complex relationship between behavior change techniques and actual behavior change [ 37 ], I.T. identity mediating meaningful interactions [ 38 ], designing strategies that address different user preferences [ 39 ], physical limitations [ 36 ], aesthetics improvement [ 40 ], effective gamification implementation [ 41 ], and consideration of usability concerns for particular user groups [ 42 ] are just a few of the issues that need to be taken into account. For gamification interventions in fitness to be implemented and used effectively, several issues must be resolved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recruitment and compliance [ 28 ], accessibility to technology and digital literacy [ 30 ], user responsiveness in particular contexts [ 22 ], ethical concerns [ 17 ], and the complex relationship between behavior change techniques and actual behavior change [ 37 ], I.T. identity mediating meaningful interactions [ 38 ], designing strategies that address different user preferences [ 39 ], physical limitations [ 36 ], aesthetics improvement [ 40 ], effective gamification implementation [ 41 ], and consideration of usability concerns for particular user groups [ 42 ] are just a few of the issues that need to be taken into account. For gamification interventions in fitness to be implemented and used effectively, several issues must be resolved.…”
Section: Resultsmentioning
confidence: 99%
“…It has become an effective way for people of all demographics to become healthier and more productive. These opportunities range from helping in the cardiorespiratory fitness of college students [ 32 ] to helping combat depression as a form of therapeutic intervention [ 40 ]. Also, research showed that gamification could increase motivation and adherence to exercise and overall fitness regimes and help individuals reach their health and fitness goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online physical activity sessions, such as virtual reality exercise (74), interactive physical-activity-based games (75), singing (76), and dance (77), have also been shown to be effective in reducing depressive and anxious symptoms.…”
Section: Physical Activity and Game-based Appsmentioning
confidence: 99%
“…Importantly, the physical performance and quality of life measures showed significant improvements after the 6 weeks session, compared to the levels seen at baseline time point. Similarly, Kim et al described a framework for use of gamification in the development of exercise-based games focussed on cardiovascular and strength training as a treatment for depression (75). The researchers are currently planning a pilot study to obtain user feedback to guide refinement of the game content.…”
Section: Physical Activity and Game-based Appsmentioning
confidence: 99%